The ironies of new innovation and the sunset industry: Diffusion and adoption - Mannan, S. (Elsevier Ltd, 2017)
Agriculture plays a vital role in the Malaysian economy. Within the agriculture sector, paddy is considered important as it is the staple food for the nation. Innovation is considered as an important and necessary component in the development of agricultural activities, while communication is the powerful tool to further strengthen this sector. Technology adoption would only take place if innovation is driven by farmers’ need. Innovation diffusion technology transfer and adoption are all inter-related facets in increasing crop production. This study examined the influence of innovation attributes, communication channels and awareness in aiding diffusion and adoption of green fertilizer technology innovation in paddy farming in Malaysia. Past innovation diffusion studies have had limited emphasis on the importance of communication for diffusion and adoption of green fertilizer technologies. Hence, there exists a gap that demands specific studies to be undertaken. This study adopted a quantitative method through survey dissemination to fulfil the aim and objective of this study. 366 paddy farmers were selected from Perak to be the respondents. Demographic and multiple regression analysis were carried out on the data. Examining these results is an important first step toward understanding factors that could make the paddy sector in Malaysia more sustainable. From the analyzed data, this study found that certain attributes which are compatibility, interpersonal communication, mass media and awareness have an influence on green fertilizer technology adoption among the local farmers in Malaysia. The results indicate that the level of farmers awareness and information about innovation in general, innovation diffusion process and the extent of attributes in innovation. The study have several implications for government agencies and policy makers in the agricultural sector. Impact of study on Malaysian context are also proposed. © 2017